Executive and social functioning in pediatric posterior fossa tumor survivors and healthy controls. Issue 2 (7th November 2022) - Ramjan, Sameera; Levitch, Cara; Sands, Stephen; Kim, Soo Young; Barnett, Marie; Bledsoe, Jesse; Holland, Alice Ann
Abstract: Background: Executive and social functioning difficulty is well established in pediatric brain tumor survivors. Few studies have compared posterior fossa (PF) tumor survivors in comparison to their peers. The relationship between attention, processing speed, working memory, fatigue, and executive and social functioning was investigated to better understand the factors that impact executive and social functioning in PF tumor populations. Methods: Sixteen medulloblastomas, 9 low-grade astrocytomas (LGAs), and 17 healthy controls recruited from 4 sites completed measures of working memory and processing speed, and self-reported fatigue. One parent completed questionnaires on executive and social functioning. Results: There were no significant differences among all 3 groups on parent-reported executive and social functioning; of note, parents of LGA survivors expressed greater concerns regarding behavioral and cognitive regulation than did parents of medulloblastoma survivors and healthy controls. Parent-reported attention was related to parent-reported emotion, behavior, and cognitive regulation. Worse self-reported fatigue was associated with greater emotional dysregulation for the 2 PF tumor groups. Conclusions: Parents of PF tumor survivors described their children as performing similarly to their peers in most facets of executive and social functioning. While LGA survivors are traditionally thought to have more favorable outcomes, our finding of parent-reported executive functioning concerns to be worse for this group highlights the importance of long-term follow-up for all PF tumor survivors. Additionally, significant effects of attention on aspects of executive functioning in PF tumor survivors may inform current clinical practice and the future development of more effective interventions.